2001
DOI: 10.1002/1096-9861(20000108)429:2<183::aid-cne1>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Transient prenatal expression of NPY‐Y1 receptor in trigeminal axons innervating the mystacial vibrissae

Abstract: Using immunohistochemistry in combination with confocal laser scanning microscopy, we studied the ontogeny of neuropeptide Y-Y1 receptor (Y1-R) expression in the trigeminal system of the rat. The study was limited to the nerve fibers innervating the mystacial pad and the trigeminal ganglia. In the trigeminal ganglia, Y1-R-immunoreactive (IR) neurons were first observed at E16.5. At this same stage some nerve fibers in the trigeminal ganglia also exhibited Y1-R-like immunoreactivity (LI). Strongly Y1-R-IR nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Interestingly, in all three studies Y1R‐LI was observed in fibers, suggesting a presynaptic localization. Although Y1Rs have been considered to be primarily postsynaptic, as originally proposed by Wahlestedt and his colleagues (1986), there is now evidence for a presynaptic localization (Peaire et al, 1997; Pickel et al, 1998; St‐Pierre et al, 2000; Kopp et al, 2002; Ubink et al, 2001; Brumovsky et al, 2002). The fact that a few enteroendocrine cells were positive for the Y1R suggests that secretion of a peptide hormone and/or biogenic amine (Polak and Bloom, 1988; Sundler and Hâkanson, 1988) in single instances may be regulated by NPY.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, in all three studies Y1R‐LI was observed in fibers, suggesting a presynaptic localization. Although Y1Rs have been considered to be primarily postsynaptic, as originally proposed by Wahlestedt and his colleagues (1986), there is now evidence for a presynaptic localization (Peaire et al, 1997; Pickel et al, 1998; St‐Pierre et al, 2000; Kopp et al, 2002; Ubink et al, 2001; Brumovsky et al, 2002). The fact that a few enteroendocrine cells were positive for the Y1R suggests that secretion of a peptide hormone and/or biogenic amine (Polak and Bloom, 1988; Sundler and Hâkanson, 1988) in single instances may be regulated by NPY.…”
Section: Discussionmentioning
confidence: 96%
“…Localization of Y1R and Y2R was studied at the histochemical level with ligand binding techniques and autoradiography, in addition to the functional/pharmacologic analysis (Pheng and Regoli, 2000; see references above). More recently, immunohistochemical studies with Y1R antibodies have so far described the distribution of the Y1R in sensory neurons (Zhang et al, 1994b, 1999; Ubink et al, 2001; Brumovsky et al, 2002), in cerebral blood vessels (Bao et al, 1997), in small arteries and arterioles in the genital tract (Kopp et al, 1997), and in blood vessels and a few enteroendocrine cells and neurons and axons in the intestine (Jackerott and Larsson, 1997; Peaire et al, 1997). In the present study, Y1R‐LI was found not only in smooth muscle cells of blood vessels but also in capillary walls, in a reticulum in the mouse spleen, and in some epithelial and endocrine cells, as will be discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…An affinity‐purified rabbit polyclonal antibody directed against a C‐terminus fragment (amino acids 370‐382) of the rat Y1 receptor (Ab 96106) was produced by the Antibody/RIA Core of the CURE/Digestive Diseases Research Center and generously provided by H. Wong and J.H. Walsh of the University of California, Los Angeles (Zhang et al, 1994; Bao et al, 1997; Ubink et al, 2001). Specificity of immunostaining was evaluated by preadsorbing the antibody with 10 −6 M synthetic Y1 370‐382 .…”
Section: Methodsmentioning
confidence: 99%
“…Walsh of the University of California, Los Angeles (Zhang et al, 1994;Bao et al, 1997;Ubink et al, 2001). Specificity of immunostaining was evaluated by preadsorbing the antibody with 10 -6 M synthetic Y1 [370][371][372][373][374][375][376][377][378][379][380][381][382] .…”
Section: Antibodiesmentioning
confidence: 99%
“…Specificity of immunostaining was evaluated by preadsorbing the antibody with 10 -6 M synthetic Y1 [370][371][372][373][374][375][376][377][378][379][380][381][382] . Specificity of immunostaining of this Y1 antibody was also evaluated by using Y1 receptor-deficient mice (Ubink et al, 2001). Sections from Y1-deficient mice did not show any specific Y1 immunoreactivity.…”
Section: Antibodiesmentioning
confidence: 99%